Ekoteologi dalam Perspektif Katolik: Studi terhadap Ayat-Ayat Pelestarian Lingkungan di Gereja Katedral Santa Maria Palembang - Suryani, Suryani; Fitriyana, Nur; Nugroho, Nugroho (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to identify problems related to the understanding and implementation of ecotheological teachings based on Genesis 1:26–28 and Psalm 24:1 in the lives of the congregation at the Santa Maria Cathedral Church in Palembang and to position ecotheology as a theological foundation for ecological responsibility. The study uses qualitative methods through interviews with informants and literature reviews from journals and articles related to Catholic ecotheology. The main findings indicate that the congregation understands ecotheology as a calling of faith that is manifested in waste management, reforestation, and involvement in church ecological programs. This study contributes to the development of theology, religious environmental studies, and pastoral practices that encourage ecological awareness. The novelty of the study lies in the integration of local empirical data and Catholic ecotheological literature, which confirms that ecological concern is a spiritual practice that shapes the behavior of the congregation.